Implications for optimizing treatment timing: day of week variation in PTSD symptom clusters - Biggs, Quinn M.; Wang, Jing; Fullerton, Carol S.; Amin, Rohul; Hooke, Joseph A.; Dhanraj, Natasha; Ursano, Robert J. (Frontiers in Psychiatry, 2025)
IntroductionPosttraumatic stress disorder (PTSD) has four symptom clusters: intrusion, avoidance, negative cognitions/mood, and hyperarousal. Little is known about day-to-day variation in the symptom clusters. If there is such variation, it highlights the need to develop more person-specific interventions. This study examined the day of the week and weekday versus weekend variation in PTSD symptom clusters in individuals with and without PTSD.MethodsUsing an ecological momentary assessment methodology, participants (N = 159; 80 with probable PTSD, 79 without PTSD) completed self-report assessments of posttraumatic stress symptoms (PTSS) four times daily for 15 days. Linear mixed models were used to examine associations between the seven days of the week and weekday versus weekend variation in PTSD symptom clusters and PTSD.ResultsAll four symptom clusters varied across the seven days of the week among participants with PTSD (intrusion: p = .038, avoidance: p <.001, negative cognitions/mood: p = .007, hyperarousal: p <.001), but not among those without PTSD. Among those with PTSD, the four symptom clusters were higher on weekdays than weekends (intrusion: p = .008, avoidance: p = .002, negative cognitions/mood: p <.001, and hyperarousal: p <.001). However, among those without PTSD, weekdays were higher than weekends only for the intrusion (p = .042) and hyperarousal (p = .017) clusters. Differences in when symptom clusters peaked were also noted.ConclusionsAmong individuals with PTSD, the four symptom clusters vary by the day of the week with more symptoms on weekdays compared to weekends. Identification of the factors associated with day-to-day variation in PTSD symptom clusters may be important for understanding the neurobiology of PTSD and for treatment.